Analysis of non-synchronous trading effects on the pricing of Exchange Traded Products: an empirical analysis of the effects on ETP price volatility that result when the ETP instrument is listed on an exchange that is in a different time zone to that of the underlying securities basket - Valle, Tarryn Sydne (Department of Finance and Tax, 2016)
Includes bibliographical references